Risk assessment and advancement in treatment in Sremska Mitrovica correctional facility - Vujičić Nikola; Karić Tijana (Anali Pravnog Fakulteta u Beogradu)
Risk assessment is one of the main areas of interest of experts dedicated to the analysis of offenders convicted to imprisonment. After theoretical assumptions, consideration of the Risk Assessment Questionnaire and relevant research in this area, we present results of an empirical study conducted in PCI Sremska Mitrovica, on a sample of 150 offenders released between 2016 and 2018. The basic hypotheses were: (1) most offenders are primarily classified into closed wards; (2) most offenders advance during the treatment into a more favorable category, and (3) those who have advanced are paroled. The hypotheses are analysed from the aspect of estimated risk based on Risk Assessment Questionnaire and being in a particular treatment group. These hypotheses have been confirmed.